2007
DOI: 10.1007/s10800-007-9377-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of optimal conditions for zinc electrowinning from aqueous sulfuric acid electrolytes

Abstract: Results are reported of an experimental investigation of the effects of aqueous zinc(II) and sulfuric acid concentrations on current efficiencies and deposit morphologies of metallic zinc, aimed at designing a process for zinc recovery from solid industrial wastes by leaching and electrodeposition. Voltammetry and chronopotentiometry of additive-free solutions of zinc(II) sulfate and sulfuric acid were used to determine the zinc(II) reduction kinetics, prior to investigating the deposition in a Hull cell to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…The metal oxide product is then leached with aqueous sulfuric acid. Leaching results in the formation of zinc sulfate in the aqueous sulfuric acid and the metal is then produced by electrodeposition [1]. However, electrodeposition of zinc is extremely sensitive to the presence of certain metallic impurities [2][3][4][5] in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…The metal oxide product is then leached with aqueous sulfuric acid. Leaching results in the formation of zinc sulfate in the aqueous sulfuric acid and the metal is then produced by electrodeposition [1]. However, electrodeposition of zinc is extremely sensitive to the presence of certain metallic impurities [2][3][4][5] in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…In the zinc-halogen batteries some of the factors that affect the zinc deposition here are the electrode substrate, the charging method, the cell geometry, the electrolyte hydrodynamics, the electrolyte composition and the zinc electrode morphology [45]. The investigation of aqueous zinc in sulfuric acid was carried out by Guillame [46] who reported that HER on stainless steel is inhibited by deposition of zinc and that the current density had little impact on the deposit morphology. The same study also reported that increasing the concentration of the zinc species (>2 × 10 −1 mol dm −3 ) yielded higher deposition current efficiencies, viz.…”
Section: Page 3 Of 25mentioning
confidence: 99%
“…It is revealed that the zinc cell house is responsible for approximately 80% of the energy used by an electrolytic zinc refinery. Thus, intensive research has been conducted to lower energy consumption or increase current efficiency per mass of zinc produced [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined optimal conditions for zinc electrowinning [3][4][5]. They utilized a variety of experimental cells and electrodes to test the effect of variables on cell performance.…”
Section: Introductionmentioning
confidence: 99%